Circadian oscillations of KaiA‐KaiC and KaiB‐KaiC complex formations in an in vitro reconstituted KaiABC clock oscillator. (1st August 2016) - Murakami, Reiko; Mutoh, Risa; Ishii, Ketaro; Ishiura, Masahiro
Abstract : The circadian clock is an endogenous biological mechanism that generates autonomous daily cycles in physiological activities. The phosphorylation levels of KaiC oscillated with a period of 24 h in an ATP‐dependent clock oscillator reconstituted in vitro from KaiA, KaiB and KaiC. We examined the complex formations of KaiA and KaiB with KaiC in the KaiABC clock oscillator by fluorescence correlation spectrometry (FCS) analysis. The formation of KaiB‐containing protein complex(es) oscillated in a circadian manner, with a single peak at 12 h and single trough at 24 h in the circadian cycle, whereas that of KaiA‐containing protein complex(es) oscillated with two peaks at 12 and 24 h. FCS and surface plasmon resonance analyses showed that the binding affinity of KaiA for a mutant KaiC with Ala substitutions at the two phosphorylation sites considered to mimic the nonphosphorylated form of KaiC (np‐KaiC) was higher than that for a mutant KaiC with Asp substitutions at the two phosphorylation sites considered to mimic the completely phosphorylated form of KaiC (cp‐KaiC). The results from the study suggest that a KaiA‐KaiB‐cp‐KaiC ternary complex and a KaiA‐np‐KaiC complex were formed at 12 and 24 h, respectively. Abstract : The phosphorylation levels of KaiC oscillated with a period of 24 h in an ATP‐dependent clock oscillator reconstituted in vitro from KaiA, KaiB and KaiC. We examined the complex formations of KaiA and KaiB with KaiC in the KaiABC clock oscillator by fluorescence correlation spectrometry analysis and showed that the formation of KaiB‐containing protein complex(es) oscillated in a circadian manner, with a single peak at 12 h and single trough at 24 h in the circadian cycle, whereas that of KaiA‐containing protein complex(es) oscillated with two peaks at 12 and 24 h.